PEMBERDAYAAN MASYARAKAT MELALUI DESTINATION BRANDING KAWASAN WISATA KULINER LAWU KAUMAN KOTA BLITAR - Sinta Rusmawati; Mu'tassim Billah; Ahmad Rifqi Utomo (DAS Institute, 2022)
Kauman Village is one of the villages in the Kepanjen Kidul District. The geographical position of Kauman, which is located close to the City Center and Blitar City Square, makes the activities of the Kauman community dominated by culinary traders and entrepreneurs. Wisata Kuliner Lawu is a sustainable tourism potential and has become one of the iconic tours in Kauman Village, which the government has inaugurated. In realizing sustainable tourism, community-based tourism is considered a critical approach to implement. This community empowerment involves and places the community as an essential actor in the context of the new development paradigm. This study discusses the role of culinary tourism in creativity and the strategies developed for Wisata Kuliner Lawu branding. This research was structured using qualitative methods and carried out using observation and interview techniques with the head of the Lawu community. From the results of the research conducted, the community service team then implemented five stages of destination branding by Morgan & Pritchard by involving local communities with community empowerment programs and supported by iconic culinary delights, namely Patria Lontong Tofu, Trotoar Lawu Fried Rice, STMJ, and Jadah Bakar Lawu